FAKTOR –FAKTOR YANG MEMPENGARUHI PERUBAHAN PERILAKU PETERNAK TERHADAP PENGOBATAN DAN PENCEGAHAN NEMATODIASIS PADA KAMBING - Supriyanto; Nurdayati; Ahadiati N (JURNAL TRITON, 2016)
The study was conducted at the Japan District of Magelang regency Tegalrejo time execution of activities in April through June 2016, with the objective to be achieved is to know the level and the factors - factors that influence changes in the behavior of farmers. Samples were taken census of members of Farmers Group "Source Rezeki", extension materials nematodiasis treatment and prevention, data collection method of observation and interviews. The rate of change is measured by the variable behavior of farmers Knowledge, Attitude, Skills (KAS). Extension method used is the method of approach to groups and individuals, through verbal counseling techniques (lectures, discussions) and demcar, projected through folders and materials (power point) as the media. Counseling was done 2 times. The rate of change of behavior analysis is comparative descriptive analysis and the factors that influence the rate of change in behavior analysis with regression analysis. Espionage was carried out resulted in the rate of change of behavior from very low (26.67) be enough (63.87). Results of regression test Anova with 0,000 α significance (P ≤ 0.01), this means that the influence of age, education, experience breeding, the number of livestock ownership and ownership of livestock together - the same very significant influence on the behavior of farmers towards the treatment and prevention of diseases nematodiasis worms. The rate of change the behavior of farmers towards the prevention and treatment of diseases of worms in goats / sheep sangt increase of the rate of change is low (26.67) be enough (65.87). Factors that very significant influence on behavior change with significant value 0,000, α (P ≤ 0.01) were age and education, while simultaneously - just the experience factor raising the number of livestock, and ownership status is not very significant influence on behavior change.